An Appraisal Analysis on Joe Biden’s Rhetoric of Gun Control - Bagas Al Fajri; Zanuwar Hakim Atmantika; Galant Nanta Adhitya (Universitas Gadjah Mada, 2022)
The recurring gun violence in the U.S. has been a prevailing issue for a long period. To tackle these, the government has implemented various policies and regulations. However, a transformation is nowhere to be seen. Having advocated for a change is Joe Biden, the president of the United States. In the light of recent unfortunate occurrences, Biden delivered a public speech that addressed this issue. This study aims to understand and thoroughly comprehend Biden’s speech using appraisal analysis, in which the elements of appraisal are used to classify the terms within Biden’s speech. This research uses qualitative methods, and it is concluded that it is clear from the performed research and supplementary data in the preceding sentence that Biden's speech contains a total of 37 evaluative items. 19 of these appraising items are positive, while 18 are negative. 19 of these appraising items are positive. This study found 12 findings for each of the appraisal parts of affect and appreciation, 7 findings of Judgment-social esteem and 6 findings of judgment-social sanction. Upon analyzing, it is found that Biden’s speech contains numerous meanings, some of which are how he is saddened by the unfortunate event, and subsequently advocates transformation on gun regulation in the future years. In conclusion, Biden’s position on gun issues as president of the U.S. is that the owner and the regulation, not the gun, are the issue.